234k views
3 votes
What is the simplified form of the following expression 7(^3√2x)-3(^3√16x)-3(^3√8x)

A) -5(^3√2x

B)5(^3√x

C) ^3√2x-6(^3√x

D) -(^3√2x)-6(3√x)

User Warlord
by
6.0k points

1 Answer

7 votes

Given expression:
7\sqrt[3]{2x}-3\sqrt[3]{16x}-3\sqrt[3]{8x}


7\sqrt[3]{2x}=7\sqrt[3]{2}\sqrt[3]{x}


3\sqrt[3]{16x}=6\sqrt[3]{2}\sqrt[3]{x}


3\sqrt[3]{8x}=6\sqrt[3]{x}


=7\sqrt[3]{2}\sqrt[3]{x}-6\sqrt[3]{2}\sqrt[3]{x}-6\sqrt[3]{x}


=7\sqrt[3]{2x}-6\sqrt[3]{2x}-6\sqrt[3]{x}


\mathrm{Add\:similar\:elements:}


=\sqrt[3]{2x}-6\sqrt[3]{x}

Therefore, correct option is C)
\sqrt[3]{2x}-6\sqrt[3]{x}.

User Iwtu
by
6.7k points